2014
DOI: 10.1021/nn5008572
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Gold Nanoparticles as Carriers for Nucleus-Based Gene Therapy Due to Size-Dependent Nuclear Entry

Abstract: The aim of this study was to determine the size-dependent penetration ability of gold nanoparticles and the potential application of ultrasmall gold nanoparticles for intranucleus delivery and therapy. We synthesized gold nanoparticles with diameters of 2, 6, 10, and 16 nm and compared their intracellular distribution in MCF-7 breast cancer cells. Nanoparticles smaller than 10 nm (2 and 6 nm) could enter the nucleus, whereas larger ones (10 and 16 nm) were found only in the cytoplasm. We then investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
247
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(266 citation statements)
references
References 50 publications
5
247
1
3
Order By: Relevance
“…42 Ultrasmall AuNPs (2 nm) as carriers for nuclear delivery of triplex-forming oligonucleotides which bind to the promoter of protooncogene c-myc for reducing the generations of c-myc RNA and c-myc protein, subsequently reduce the viability of MCF-7 breast cancer cells. 43 It also demonstrated that NPs smaller than 10 nm could enter the nucleus for intranuclear delivery and therapy, whereas larger ones were found only in the cytoplasm. Although all kinds of polymer-coated AuNPs have been developed to load more nucleotides or to deliver combinations of genetic therapies to cancer cells, 44 there are still rare examples of using AuNPs-oligonucleotides conjugates for gene theranostics in vivo.…”
Section: Aunps-based Gene Therapymentioning
confidence: 99%
“…42 Ultrasmall AuNPs (2 nm) as carriers for nuclear delivery of triplex-forming oligonucleotides which bind to the promoter of protooncogene c-myc for reducing the generations of c-myc RNA and c-myc protein, subsequently reduce the viability of MCF-7 breast cancer cells. 43 It also demonstrated that NPs smaller than 10 nm could enter the nucleus for intranuclear delivery and therapy, whereas larger ones were found only in the cytoplasm. Although all kinds of polymer-coated AuNPs have been developed to load more nucleotides or to deliver combinations of genetic therapies to cancer cells, 44 there are still rare examples of using AuNPs-oligonucleotides conjugates for gene theranostics in vivo.…”
Section: Aunps-based Gene Therapymentioning
confidence: 99%
“…Au NPs have unique optical properties, biocompatibility and ease of functionalization that makes them particularly suitable in drug delivery, 95,99,148 controlled DNA release, [149][150][151] active tumour targeting, 52,118,144 photodynamic therapy (PDT) 94,152 and PTT. 92,98,100,153 Additionally, the use of NPs in these applications provides enhanced signals in Raman imaging and allows the processes to be monitored using SERS.…”
Section: [H1] Key Advances In In Vivo Sensingmentioning
confidence: 99%
“…Partially acetylated Dendrimer-entrapped gold nanoparticles (AuDENPs) delivery system was also proposed for safe gene delivery biomedical approach with improved gene transfection efficiency [19]. Recently, gold nanoparticles conjugated c-myc promoter-triplex-forming oligonucleotide (TFO) and cationic gold nanoparticles were used for improved transgene expression efficacy and intranucleus non-viral gene delivery biomedical tools [20,21].…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 99%